DAMPAK TEKNOLOGI DAN KOMUNIKASI DIGITAL TERHADAP TRANSFORMASI PENDIDIKAN DI ERA MODERN: Digital Communication; Educational Transformation; Technology - Sr Yanti; Sarmini; Ngaliman; Dimas Rio Nugroho; Sania Davina Putri (Universitas Batam, 2026)
Digital technology and communication have had a significant impact on today's education. Both developments have had both positive and negative impacts, affecting learning, teaching, and interaction within the educational environment. The purpose of this study is to determine the impact of digital technology and communication on educational transformation in the modern era. The method used in this study is library research. This method applies an approach aimed at researching and analyzing literature related to a specific topic. The research was conducted collaboratively by three lecturers and two students.